Effects of active and passive recovery conditions on blood lactate, rating of perceived exertion, and performance during resistance exercise - Corder, K. P.; Potteiger, J. A.; Nau, K. L.; Figoni, S. F.; Hershberger, S. L. (The Journal of Strength and Conditioning Research, 2000)
Authors investigated the effects of passive and active recovery on blood [La], rating of perceived exertion (RPE), and performance during a resistance training workout. Fifteen resistance-trained males completed 3 workouts, each consisting of 6 sets of parallel squat exercise performed at 85% of 10 repetition maximum (10RM). Each set was separated by a 4-minute recovery period. Recovery was randomly assigned from the following: passive sitting; pedaling at 25% of onset of blood lactate accumulation (OBLA) exercise intensity (25%-OBLA); and pedaling at 50% of OBLA exercise intensity (50%-OBLA). Active recovery was performed on a bicycle ergometer at 70 rev·min1. Performance was determined postworkout by a maximal repetition performance (MRP) squat test using 65% of 10RM. Blood samples were collected: prewarm-up; postsecond, postfourth, postsixth, and MRP sets; and postsecond, postfourth, and postsixth recovery periods. Significant differences (p 0.05) were observed in [La], and RPE among the 3 recoveries, with 25%-OBLA lower than passive and 50%-OBLA. Total repetitions to exhaustion for the MRP were: passive (24.1 ± 1.8); 25%-OBLA (29.3 ± 1.8); and 50%-OBLA (23.1 ± 1.7), with 25%-OBLA being significantly greater than passive and 50%-OBLA. In this investigation, active recovery at 25%-OBLA proved to be the most effective means of reducing [La] during recovery and increasing performance following a parallel squat workout.